EFISIENSI USAHATANI PADI SAWAH (Oryza sativa L.) DI DESA TANAH ABANG KECAMATAN LONG MESANGAT KABUPATEN KUTAI TIMUR (Efficiency of Paddy Farming (Oryza sativa L.) in Tanah Abang Village Long Mesangat Subregency East Kutai Regency) - MURKAD MURKAD; MURSIDAH MURSIDAH; NIKE WIDURI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
Tanah Abang Village is a region of paddy farming development.  The purposes of this study were to know the cost, revenue, income, production, and efficiency of paddy farming in Tanah Abang Village. This study was conducted during three months from January to March 2018 in Tanah Abang Village, Long Mesangat Subregency, East Kutai Regency. Sampling was done with stratified random sampling method with total of 37 respondents. Data retrieving was done by interview and field observation. Data analysis was done to count of fixed cost, variable cost, total cost, revenue, income, and R/C ratio. The results of study show that the production of 2,168.92 kg cropping season (cs)-1 ha-1, the revenue of IDR13,966,622.00 cs-1 ha-1, the income of IDR12,437,394.00 cs-1 ha-1, and R/C ratio 7.37 which meant paddy farming is efficient and feasible to be done.